Analyzing Public Sector Accounting Standards: A Qualitative Synthesis of Literature - Prabowo, Bambang Hadi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This qualitative synthesis aims to provide a comprehensive overview of public sector accounting standards, focusing on their definitions, specificities, challenges, and implications. The research objective is to analyze existing literature to identify key themes, trends, and areas for further inquiry in public sector accounting. A systematic review of relevant studies was conducted, with data extracted and analyzed to derive insights into accountability, transparency, accrual basis of accounting, adoption of International Public Sector Accounting Standards (IPSAS), challenges, opportunities, and implications for future research. The findings reveal that robust accounting standards are crucial for ensuring transparency and accountability in governmental entities. Adoption of accrual accounting enhances the accuracy and relevance of financial reporting, while the convergence towards IPSAS facilitates comparability and consistency across jurisdictions. Challenges include capacity constraints, resistance to change, and keeping pace with evolving regulatory environments. However, opportunities exist in leveraging technology, increasing collaboration, and investing in professional development. Future research should focus on longitudinal studies, comparative analyses, interdisciplinary approaches, stakeholder perceptions, and the role of emerging technologies in public sector accounting. This synthesis contributes to the scholarly discourse by providing insights into the complexities and implications of public sector accounting standards.